FOTODEGRADASI FENOL MENGGUNAKAN FOTOKATALIS TiO2-Zeolit DAN SINAR UV - Yeslia Utubira; Melvie Talakua (Molluca Journal of Chemistry Education (MJoCE), 2011)
The photodegradation of Phenol using TiO2-Zeolite and UV systems have been investigated. The preparation of titan oxide-zeolite composite has been done by dispersing oligocation of titanium solution into suspension of natural zeolite and the solid phase was heating by microwave oven at 800 Watt for 5 minutes. Characterization results exhibited that the formation of TiO2 on internal as well as external surfaces of zeolite could not be detected with x-ray diffractometry and FT-IR spectrophotometry, however elemented analysis result with XRF indicated titan content increased from 0.26% (w/w) in zeolite to 2.80% (w/w) in TiO2-zeolite. Characterization result by GSA exhibited the increased of specific surface area from 19.57 m2/g in zeolite to 67.96 m2/g in TiO2-zeolite; total pore volume from 20.64 x 10-3 mL/g in zeolite to 49.561 x 10-3 mL/g in TiO2-zeolite; pore radius average decreased from 21.10 Ã… in zeolite to 14.58 Ã… in TiO2-zeolite. Photocatalytic activity of TiO2-zeolit for degradation phenol showed that in 75 minutes UV radiation resulted in the decreased concentrate up to 44.29%. Meanwhile the sorption study showed that photocatalyst TiO2-zeolite caused the decrease of concentrate up to 17.9%.